WAYS OF EFFECTIVE USE OF MODELING METHODOLOGY IN THE DEVELOPMENT OF SEMIOTICS IN MATHEMATICS IN YOUNG STUDENTS - Abdusamatov Alisher Sobirovich (Zeta Repository, 2023)
In this article, the importance of semiotic aspects in teaching mathematics to young students, its applications, the necessary pedagogical conditions, the scientists and their views are described in detail, the branches, directions of semiotics and how we can use it in our daily life. passed.